2016
DOI: 10.3389/fnhum.2016.00578
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Sensorimotor Processing of Painful Pressure in Patients with Chronic Lower Back Pain—An Optical Neuroimaging Study using fNIRS

Abstract: In this study we investigated sensorimotor processing of painful pressure stimulation on the lower back of patients with chronic lower back pain (CLBP) by using functional near-infrared spectroscopy (fNIRS) to measure changes in cerebral hemodynamics and oxygenation. The main objectives were whether patients with CLBP show different relative changes in oxy- and deoxyhemoglobin ([O2Hb] and [HHb]) in the supplementary motor area (SMA) and primary somatosensory cortex (S1) compared to healthy controls (HC). Twelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…The median values calculated across a distinct task period are less influenced by outliers as compared to mean or peak values [278]. As frequently shown [72,210,211,212,271], median values are best suited in fNIRS studies with small sample sizes that are otherwise prone to statistical effects driven by outliers [278]. However, Khan and colleagues [279] propose that several measurement parameters should be provided (e.g., mean signal value, signal peak, and the sum of peaks) in order to best describe the brain state [279].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median values calculated across a distinct task period are less influenced by outliers as compared to mean or peak values [278]. As frequently shown [72,210,211,212,271], median values are best suited in fNIRS studies with small sample sizes that are otherwise prone to statistical effects driven by outliers [278]. However, Khan and colleagues [279] propose that several measurement parameters should be provided (e.g., mean signal value, signal peak, and the sum of peaks) in order to best describe the brain state [279].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to the FIR/IIR bandpass filter, we recommend the use of the Savitzky-Golay filter [209], which is widely applied in fNIRS studies [210,211,212] and ensures that mostly non-related components of the evoked hemodynamic response could be removed, whereas task-related components are preserved [213]. Furthermore, the data obtained from resting-state functional connectivity could also be used to substantially reduce trial-to-trial variability (e.g., arising from low-frequency spontaneous fluctuations) in fNIRS studies [214].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously used to denoise fNIRS signal. 25,26 Rloess combines weighted linear least squares regression with the flexibility of nonlinear regression. 27 In several fNIRS studies, Rloess has been used as a smoothing filter in data preprocessing.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, previous studies have also found that S1 is activated during pain experience 10 , 20 , 22 , 23 , 44 and that the dysfunction of the S1 cortex in migraineurs may affect nociception pathways. 45 Furthermore, peripheral nerve injury can indeed elicit rapid and dynamic neural circuit rewiring in the S1 area.…”
Section: Discussionmentioning
confidence: 95%